2022
DOI: 10.3390/antiox11122444
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A11 as a Gateway of Metabolic Perturbation and Ferroptosis Vulnerability in Cancer

Abstract: SLC7A11 is a cell transmembrane protein composing the light chain of system xc−, transporting extracellular cystine into cells for cysteine production and GSH biosynthesis. SLC7A11 is a critical gateway for redox homeostasis by maintaining the cellular levels of GSH that counter cellular oxidative stress and suppress ferroptosis. SLC7A11 is overexpressed in various human cancers and regulates tumor development, proliferation, metastasis, microenvironment, and treatment resistance. Upregulation of SLC7A11 in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…77 The SLC7A11-ALOX12 axis is independent of GSH level and the antioxidant activity of GPX4. 78,79 In our study, the suppression of SLC7A11 and GPX4 was observed as well as the reduction of GSH biogenesis, which are convincing and solid evidence that lepadins E and H induce ferroptosis through the classical p53-SLC7A11-GPX4 pathway. Additionally, lepadins E and H were found to increase ACSL4 protein expression, indicating the upregulation of ACSL4 may also contribute to the ferroptosis of Hela cells.…”
Section: Discussionsupporting
confidence: 83%
“…77 The SLC7A11-ALOX12 axis is independent of GSH level and the antioxidant activity of GPX4. 78,79 In our study, the suppression of SLC7A11 and GPX4 was observed as well as the reduction of GSH biogenesis, which are convincing and solid evidence that lepadins E and H induce ferroptosis through the classical p53-SLC7A11-GPX4 pathway. Additionally, lepadins E and H were found to increase ACSL4 protein expression, indicating the upregulation of ACSL4 may also contribute to the ferroptosis of Hela cells.…”
Section: Discussionsupporting
confidence: 83%
“…SLC7A11 helps counteract oxidative stress and inhibit ferroptosis by maintaining cellular GSH levels. Studies have shown that high expression of SLC7A11 is closely related to cisplatin resistance in bladder cancer ( 51 , 52 ). Experimental and bioinformatics studies have also demonstrated that the level of SLC3A2 protein is significantly elevated in bladder cancer tumor cells compared to non-cancerous bladder epithelial cells, suggesting that SLC3A2 may serve as a useful tumor tissue marker for the diagnosis of bladder cancer patients ( 53 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, we found that ME with heavy glial/vascular contributions increased considerably toward the lesion edge when ME19 and 13 decreased drastically from their peak at the lesion core ( Fig2E ). For example, genes that suppress ferroptosis ( AIFM2 , MGST1 , (62,63)) are enriched in ME19, 13, 8, 18 ( FigS7 ), whereas genes that induce ferroptosis ( SLC7A11 , TMEM164 , (64,65)) are expressed by AST, VLMC, and ependyma of ME group iv, which is significantly enriched in perilesional WM compared to intralesional WM ( FigS5C ). Together, this suggests a transition from immune (intralesional WM) to glial/vascular (perilesional WM)-dominant ME with a mixture of destructive and protective signals as lesions evolve, and we further deconvolute this complexity in the following sections.…”
Section: Mainmentioning
confidence: 99%